Comparison of Three-Phase Rectifier with Symmetrical Switching and AC-AC Converter for the Power Factor Improvement in Hydroelectric Micro-Plants - Henry Bory Prevez; Herminio Martínez García; Luís Vázquez Seisdedos; Francisco Chang Mumañ; Lorenzo Alfredo Enríquez García (Revista Iberoamericana de Automática e Informática Industrial RIAI)
Many of hydroelectric micro-plants, useful for the electricity production at intricate regions, operate in autonomous regimen. Therefore, it is necessary to accomplish the control of frequency. One way to control the frequency is varying the power dissipated in ballast loads employing AC-AC converters. These converters consume reactive power, contributing to aggravate the power factor at the generator output. An alternative in order to avoid the deterioration of the power factor is the use of a bridge three-phase rectifier using diodes with a serial switch with the load that is switched with symmetric angle. As a consequence, the objective of this article is to carry out a comparison between the aforementioned three-phase rectifier and the AC-AC converter, regarding the power factor at the output of the electric generator of hydroelectric micro-plants that regulate frequency by means of the ballast-load method.